KENDALA KECEPATAN PENGIRIMAN DAN PEMBELIAN DI E-COMMERCE - Widya Aulia Rahmawati; Ani Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2023)
People's shopping behavior has now shifted from offline to online. The online shopping trend has given rise to a new business called e-commerce. E-commerce is starting to develop in Indonesia, and competition between e-commerce providers is getting tighter. Therefore, a marketing communications strategy is needed to win competition in e-commerce, including the introduction of quality e-services. Implementing high-quality e-services increases customer satisfaction. The importance of the impact of electronic service quality on e-commerce consumer satisfaction. Academically, this research further develops communication research, especially on the topic of changing the cognitive behavior of e-commerce consumers in Indonesia, as well as improving the quality and satisfaction of consumers in advancing, maintaining and improving the quality and satisfaction of e-commerce consumers in Indonesia. The practical benefits obtained through the marketing communications strategy team can consider/implement any elements in e-commerce that can attract the attention of digital consumers.